Хранитель найбільшого у світі радіотелескопа (інтерв’ю до 70-річчя академіка НАН України О. О. Коноваленка) (Вісник НАН України, 2021)
27 лютого виповнюється 70 років відомому вченому в галузі радіоастрономії і астрофізики, лауреату Державної премії України в галузі науки і техніки (2018), лауреату Державної премії СРСР (1988), заслуженому діячеві
науки і техніки України (2001), лауреату іменних премій НАН України:
імені С.Я. Брауде (2008) та імені М.К. Янгеля (2013), керівнику відділення
низькочастотної радіоастрономії — заступнику директора Радіоастрономічного інституту НАН України (з 2007), доктору фізико-математичних наук (1984), академіку НАН України (2003) Олександру Олександровичу Коноваленку. Користуючись нагодою, редакція журналу «Вісник НАН
України» взяла інтерв’ю у ювіляра і розпитала про його шлях у науці, найбільші досягнення та плани на майбутнє. February 27 marks the 70th anniversary of the famous scientist in the field of radio astronomy and astrophysics, laureate
of the State Prize of Ukraine in Science and Technology (2018), laureate of the USSR State Prize (1988), Honored
Worker of Science and Technology of Ukraine (2001), laureate of the NAS of Ukraine Prizes named after S.Ya. Braude
(2008) and M.K. Yangel (2013), Head of the Department of Low-Frequency Radio Astronomy, Deputy Director of the
Radio Astronomical Institute of the NAS of Ukraine (since 2007), Doctor of Physics and Mathematics (1984),
Academician of the NAS of Ukraine (2003) Olexander O. Konovalenko. Taking the opportunity, the editorial board of
the Visnyk of the National Academy of Sciences of Ukraine interviewed Academician O.O. Konovalenko and asked
about his path in science, his greatest achievements and plans for the future.